Communication, education, and information on non-communicable diseases - Chaedyr Iqbal; Muh Ihsan Kamaruddin; Wa Ode Novi Angreni; A Syamsinar Asmi; Qalbia Muhammad Nur (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2024)
Non-communicable diseases (NCDs) such as diabetes mellitus, hypertension, and heart disease continue to increase in Indonesia, threatening public health and adding to the country's economic burden. Efforts to control NCDs require an integrated approach, one of which is through community service programs that focus on communication, education, and information (KIE). This community service program aims to increase public awareness and knowledge about NCDs, especially diabetes mellitus, by involving various parties, including academics, health workers, and local communities. The methods used in this program include health counseling, campaigns through social media, and interactive training in various villages and sub-districts. The results of this program show a significant improvement in public understanding of risk factors, early signs, and NCD prevention measures. The active participation of the community in this activity also strengthens collective awareness about the importance of a healthy lifestyle and regular health checkups. This program has succeeded in having a positive impact on efforts to prevent and control NCDs in the community. The recommendations of this program include expanding the reach of KIE activities, wider use of information technology, and continuous collaboration between various sectors to create a healthier society.